Dissecting the Local Environment of FRB 190608 in the Spiral Arm of its Host Galaxy - Chittidi, J.S.; Simha, S.; Mannings, A.; Prochaska, J.X.; Ryder, S.D.; Rafelski, M.; Neeleman, M.; Macquart, Jean-Pierre; Tejos, N.; Jorgenson, R.A.; Day, C.K.; Marnoch, L.; et al. (IOP Publishing Ltd, 2021)
We present a high-resolution analysis of the host galaxy of fast radio burst (FRB) 190608, an SB(r)c galaxy at z = 0.11778 (hereafter HG 190608), to dissect its local environment and its contributions to the FRB properties. Our Hubble Space Telescope Wide Field Camera 3 ultraviolet and visible light image reveals that the subarcsecond localization of FRB 190608 is coincident with a knot of star formation (ΣSFR = 1.5 × 10-2 M⊙ yr-1 kpc-2) in the northwest spiral arm of HG 190608. Using Hβ emission present in our Keck Cosmic Web Imager integral field spectrum of the galaxy with a surface brightness of μHβ=(3.36 ± 0.21)× 10-17 erg s-1 cm-2 arcsec-2, we infer an extinction-corrected Hα surface brightness and compute a dispersion measure (DM) from the interstellar medium of HG 190608 of DMHost,ISM = 94 ± 38 pc cm-3. The galaxy rotates with a circular velocity vcirc = 141 ± 8 km s-1 at an inclination igas = 37° ± 3°, giving a dynamical mass Mhalodyn ≈ 1011.96±0.08 M⊙. This implies a halo contribution to the DM of DMHost,Halo = 55 ± 25 pc cm-3 subject to assumptions on the density profile and fraction of baryons retained. From the galaxy rotation curve, we infer a bar-induced pattern speed of Ωp = 34 ± 6 km s-1 kpc-1 using linear resonance theory. We then calculate the maximum time since star formation for a progenitor using the furthest distance to the arm's leading edge within the localization, and find tenc = 21-6+25 Myr. Unlike previous high-resolution studies of FRB environments, we find no evidence of disturbed morphology, emission, or kinematics for FRB 190608.